Analysis of tour package branding on customer re-purchase intention at Cahaya Amanah tour and travel - Aisa Fadilla Putri; Irwan Yulianto (University of Merdeka Malang, 2025)
This research aims to analyze the influence of tour package branding on customers’ repeat purchase decisions at Cahaya Amanah Tour and Travel, located in Tambakrejo, Tambakasri, Tajinan District, Malang Regency. In the increasingly competitive tourism industry, branding plays a crucial role in shaping brand image, trust, perceived quality, and differentiation—factors that significantly affect customer loyalty and the likelihood of repeat purchases. This study uses a quantitative method with an explanatory approach. The population includes customers who have previously used the tour services of Cahaya Amanah Tour and Travel, with a sample size of 100 respondents determined using the Slovin formula. Data was collected through closed questionnaires and analyzed using multiple linear regression. The results indicate that branding dimensions—including brand image, brand trust, perceived quality, and differentiation—simultaneously have a significant effect on repeat purchase decisions. Partially, brand image, brand trust, and differentiation have a significant effect, while perceived quality does not significantly affect repeat purchasing. These findings suggest that strong and strategic branding has the potential to enhance customer retention. Therefore, Cahaya Amanah Tour and Travel is encouraged to consistently strengthen its branding across all service aspects.